Assessing dairy farming eco-efficiency in New Zealand: a two-stage data envelopment analysis. Issue 3 (3rd July 2021) - Soliman, Tarek; Djanibekov, Utkur
ABSTRACT: We employ a two-stage data envelopment analysis technique to assess the ecological-economic performance or 'eco-efficiency' of dairy farms in New Zealand. 108 dairy farms were surveyed over one year period across the country to analyse farming eco-efficiency. Survey data on milksolids production and production costs are used to estimate the economic performance (i.e. profits), while data on greenhouse gas emissions and estimated nutrient leaching are used to analyse environmental performance. Information on geophysical characteristics and management practices that could indirectly affect farm eco-efficiency, is also incorporated into the analysis. In the first stage, we estimate eco-efficiency scores for each sampled farm using data envelopment analysis which estimates the maximum possible reductions in environmental outputs while retaining the current level of profits. In the second stage, the effects of geophysical characteristics and management practices on the calculated eco-efficiency scores are estimated using an integrated truncated regression and bootstrapping procedure. The results show that, on average, a reduction of 27% in adverse environmental externalities is achievable while maintaining the same level of economic output. Adopting on-farm management practices can be an option to improve dairy efficiency. In addition, soil topography and higher temperatures are associated with reduced levels of eco-efficiency.